Trends of extinction risk for Lepidoptera in Finland: the first national Red List Index of butterflies and moths. Issue 2 (9th December 2015) - Juslén, Aino; Cardoso, Pedro; Kullberg, Jaakko; Saari, Sanna; Kaila, Lauri
Abstract: The Finnish Red Lists from 2000 and 2010 were used to calculate for the first time the national Red List Index for the order Lepidoptera and different Lepidoptera families with data from 2245 species. We grouped species according to their primary habitats and analysed each habitat's RLI as well. The overall RLI was significantly negative, reflecting the worsening of the group as a whole in the country. A significant negative trend was found for families Tortricidae, Gelechiidae and Hesperiidae and for coastal habitats. We also report that 76 Lepidoptera species newly established a population in Finland between 2000 and 2010, probably expanding northwards driven by climate warming.